Is it possible to prevent morbidity on post cardiovascular surgery applying low level laser therapy? - Pinto, Nathali C.; Baptista, Ivany Machado D. C. [UNESP]; Pereira, Mara Helena C.; Serrão, Nelson F.; Pomerantzeff, Pablo M. A.; Chavantes, Maria Cristina (SPIE, the international society for optics and photonics, 2014)
Background and Objective: Complications following cardiovascular surgery incision are common in mediastinitis and wound dehiscence form, a 47% mortality rate remaining. Low Level Laser Therapy (LLLT) has been employed mainly to its effectiveness analgesic and anti-inflammatory actions, aiding the tissue repair process. The aim of this study was to evaluate infrared LLLT onto surgical incision in patients submitted to cardiovascular surgery. Materials and Methods: 40 patients were divided in two groups: Placebo Group (G1) - conventional therapy + Laser pointera and Laser Group (G2) - conventional therapy + Infrared Laser irradiation on surgical incision. Diode Laser was employed, C.W. mode, around the surgical wound bed, on immediate Post Operative (PO), 1st PO and 3rd PO with the following parameters: wavelength (λ): 830nm, P=35mW, E=0,75J. Results: G2 didn't present any complication and 5% of patients in G1 developed incision dehiscence and infection. On 7thPO, still a large amount of G1 patients showed pain and unquestionable inflammatory signs surrounding the surgical wound, when compared to G2. Besides, hospital stay in Laser Group was 2 times shorter than in Placebo Group (p-value=0.001). Conclusion: Infrared Laser denoted to be safe and exceptionally valuable tools in preventing morbidities on post cardiovascular surgeries. © 2014 SPIE.
Keywords: Cardiovascular surgery; Low level laser therapy; Post operative; Preventive treatment